User Interface and User Experience Design for TUS Mart Sales Report Dashboard Using Design Thinking Method - Novika, Norma; Putra, Perdana Suteja; Zunaidi, Rizqa Amelia; Hidayati, Sri; Mardhiana, Hawwin; Chandra, Huki; Nafis, Ali Akbar (P3M Politeknik Negeri Bengkalis, 2024)
Digital technology is now increasingly developing in the sales sector, facilitating various activities, including buying and selling transactions. One important technology is the dashboard, which is used by buyers to place orders and by sellers to manage transactions and products. Telkom University Surabaya has developed an online shopping platform, TUS Mart, to market hydroponic and aquaponic products that are ready for harvest. In addition to functioning as a sales tool, TUS Mart also needs a dashboard to monitor and manage product stocks more efficiently. This dashboard development research involves several stages, such as understanding user needs through interviews and System Usability Scale (SUS), defining problems, generating solution ideas, and developing prototypes. Testing the prototype with SUS showed an average score of 53.125, indicating marginal performance with an “OK” rating. The findings highlight the need for improvements to the dashboard design to increase user satisfaction. This research also emphasizes the importance of the Design Thinking approach in creating design solutions centered on user needs and improving user experience in online sales systems.